2012
DOI: 10.1021/jz3003266
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientation in Stable Glasses of Indomethacin

Abstract: Spectroscopic ellipsometry has been used to measure the properties of indomethacin prepared by physical vapor deposition at Tsubstrate/Tg = 0.78, 0.84, and 0.90. The as-deposited glasses exhibited high kinetic stability and had densities 0.8-1.2% higher than the ordinary glass prepared by cooling the liquid at 1 K/min. Deposition at the higher temperatures yielded glasses with positive birefringence (up to Δn = 0.028), while the lowest-temperature sample was negatively birefringent (Δn = -0.015). These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 31 publications
9
111
0
Order By: Relevance
“…In fact, some glasses obtained by physical vapor deposition show evidence of molecular anisotropy which is partly due to the growth method of thin films from the vapor phase. In particular, ultrastable IMC glasses exhibit an extra, low-q, peak in wide-angle x-ray scattering (WAXS) spectra [44] and birrefrigence in ellipsometric measurements [45]. In our experiments [9] we have shown that the low-q peak appears indeed in the WAXS pattern of our vapor-deposited ultrastable glass, whereas it is absent in the conventionally prepared glass.…”
Section: Discussionmentioning
confidence: 57%
“…In fact, some glasses obtained by physical vapor deposition show evidence of molecular anisotropy which is partly due to the growth method of thin films from the vapor phase. In particular, ultrastable IMC glasses exhibit an extra, low-q, peak in wide-angle x-ray scattering (WAXS) spectra [44] and birrefrigence in ellipsometric measurements [45]. In our experiments [9] we have shown that the low-q peak appears indeed in the WAXS pattern of our vapor-deposited ultrastable glass, whereas it is absent in the conventionally prepared glass.…”
Section: Discussionmentioning
confidence: 57%
“…In particular, ultrastable IMC glasses exhibit an extra, low-q, peak in wide-angle X-ray scattering (WAXS) spectra (25) and birefringence in ellipsometric measurements (26). Also, computer simulations of "stable" glasses of trehalose revealed a distinct layered structure along the direction normal to the substrate that was absent in the "ordinary" glass (27).…”
Section: Resultsmentioning
confidence: 99%
“…31 In this context, we established in a previous work 27 that the growth front velocity of a transforming glass of IMC could not be determined considering only its limiting fictive temperature, but two different dependences arose, depending on whether the glass was deposited above or below 0.85T g . According to previous studies, 8,32,33 IMC vapour deposited glasses exhibit certain molecular anisotropy that depends on the deposition conditions. From the correlation between growth front velocity and molecular anisotropy in IMC glassy films, it was inferred that the arrangement of the molecules in the glass can also play a role in the transformation velocity.…”
Section: Introductionmentioning
confidence: 89%